STRENGTHENED WOODEN DOUBLE-T IN A LOW-HEIGHT BUILDING (Collection of scientific works «Modern structures of metal and wood», 2019)
Prefabricated wooden housing with the use of wooden double-T beams made of wooden glued laminated lumber and ОSВ board (oriental strand board) - a new technology that is developing very fast today. High mechanical strength and resistance to external influences (including moisture) allows using OSB in any area of activities. Traditionally, when using such beams in the overlappings, a simplified beam framing is used, which is associated with limited bearing capacity and the pitch of beams within 400-500 mm. For the possibility of using beams as part of a normal beam framing, it is proposed to reinforce the beams with double-sided steel sheet linings on the screws in places of maximum effort and to adhere to other beams. To analyze the stress-strain state of the double-T beam in the software complex "LIRA-SAPR" a spatial computer model was developed. The stress-strain state of the beam was analyzed by displacement and stress fields, as well as by deformations of the structure. At the 1st stage, the double-T beam was calculated without steel plates reinforcing. At the 2nd stage with plates in the index zone, at the 3rd stage - with plates in the index zone and in the middle of the span. Analysis of pressure distribution in beam elements along the length and intersection of a component of a double-T beam has shown the effectiveness of a structural solution of glued wooden double-T beams reinforced with steel plates for low-height construction. The reinforcement of beams with steel plates in the span, with the formation of a box section, will allow realizing the beam framing of the normal type with the connection of beams in one level. Strengthening of beams with steel plates with the formation of box sections, in areas of maximum effort, increases their rigidity and spatial stability of the beam framing.